Metabolic Responses of a Model Green Microalga Euglena gracilis to Different Environmental Stresses - He, Jiayi; Liu, ChenChen; Du, Mengzhe; Zhou, Xiyi; Hu, Zhangli; Lei, Anping; Wang, Jiangxin (Frontiers in Bioengineering and Biotechnology, 2021)
Euglena gracilis, a green microalga known as a potential candidate for jet-fuel producers and new functional food resources, are highly tolerant to antibiotics, heavy metals and other environmental stresses. Its cells contain many high-value products, including vitamins, amino acids, pigments, unsaturated fatty acids, and carbohydrate paramylon as metabolites, which change contents in response to various extracellular environments. However, mechanism insights into Euglena's cellular metabolic response to different toxic chemicals and adverse environmental stresses were very limited. We extensively investigated the changes of cell biomass, pigments, lipids, and paramylon of E. gracilis under several environmental stresses, such as heavy metal CdCl2, antibiotics paromomycin, and nutrient deprivation. Also, global metabolomics by UHPLC- LC-MS/MS was applied to study other metabolites and potential regulatory mechanisms behind the differential accumulation of major high valued metabolites. This study collects a comprehensive update on the biology of E. gracilis for various metabolic responses to stress conditions and it will be of great value for Euglena cultivation and high-value metabolite production.